Business combinations under common control (Part 2) - TAN, Pearl Hock-neo (Institutional Knowledge at Singapore Management University, 2021)
In Part 1 of the article, published in the March issue of this IS Chartered Accountant Journal, we explained the conditions for a BCUCC and the two methods of accounting for BCUCC. We also explained how accounting standards need to address the gap in accounting for the BCUCC from the receiving entity’s perspective. In this Part 2 of the article, we propose a contextual approach in determining the accounting method on BCUCC for the receiving entity (that is, the entity which receives control of the transferred entity from another group entity). We propose that a BCUCC that has commercial substance and which results in a change in the timing, amount and variability of cashflows of the receiving entity and its subsidiaries should be accounted as an acquisition under IFRS 3. The acquisition method better serves the information needs of the non-controlling interests and external stakeholders of the receiving entity when there is a real economic change of the receiving entity and its sub-group. We illustrate this point in the case study below. The lack of arm’s-length pricing does not pose insurmountable measurement issues and should not be the basis for the accounting choice.